2007
DOI: 10.1007/s11154-007-9061-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of acromegaly: Is there a role for primary medical therapy?

Abstract: Acromegaly is a chronic, debilitating disease caused by chronic growth hormone (GH) hypersecretion which results in chronic medical comorbidities, poor quality of life and high mortality rates. Successful treatment can improve clinical signs and symptoms and normalize mortality rates. Over 95% of acromegaly is caused by a somatotroph adenoma of the pituitary, and the first-line treatment is generally transsphenoidal surgery, which can be curative in 50-60% of patients. Nonetheless, high rates of persistent acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 97 publications
(183 reference statements)
0
32
0
Order By: Relevance
“…A significant proportion of patients with large macroadenomas extending outside the sella will experience persistently elevated GH levels postoperatively, often requiring subsequent medical therapy and/or radiosurgery to gain satisfactory biochemical control. 5,18 Some authors have argued primary medical therapy may be used for patients with GH-secreting macroadenomas with extrasellar extension, which makes complete surgical resection unfeasible. 5,18 However, other authors have asserted that initial operative debulking of these macroadenomas may increase the proportion of patients that subsequently attain hormonal control with adjunctive therapy, particularly if more than 75% of the initial tumor volume is resected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion of patients with large macroadenomas extending outside the sella will experience persistently elevated GH levels postoperatively, often requiring subsequent medical therapy and/or radiosurgery to gain satisfactory biochemical control. 5,18 Some authors have argued primary medical therapy may be used for patients with GH-secreting macroadenomas with extrasellar extension, which makes complete surgical resection unfeasible. 5,18 However, other authors have asserted that initial operative debulking of these macroadenomas may increase the proportion of patients that subsequently attain hormonal control with adjunctive therapy, particularly if more than 75% of the initial tumor volume is resected.…”
Section: Discussionmentioning
confidence: 99%
“…5,18 Some authors have argued primary medical therapy may be used for patients with GH-secreting macroadenomas with extrasellar extension, which makes complete surgical resection unfeasible. 5,18 However, other authors have asserted that initial operative debulking of these macroadenomas may increase the proportion of patients that subsequently attain hormonal control with adjunctive therapy, particularly if more than 75% of the initial tumor volume is resected. 17,35,48,54 To demonstrate safety and efficacy an attempt was made to carefully evaluate and report the biochemical results of endoscopic resection of GH-secreting adenomas in the current series.…”
Section: Discussionmentioning
confidence: 99%
“…An endocrinological "cure" for acromegaly, as defined by the stringent criteria of biochemical remission 10,21) , was achieved in 64% of patients, similar to that reported in the most recent series 16,[19][20][21]25) . TSS remains an effective treatment for acromegaly, whereas medical treatment and/or radiotherapy should be reserved for patients with persistent GH/IGF-I hypersecretion after surgery 4) . However, for patients with cavernous sinus invasion of Knosp grade III and IV 15) , invasive GH-secreting pituitary adenoma may be unresectable due to the involvement with structures of the cavernous sinus; the GH level can't be normalized, the surgical cure rate is low while the incidence of complications is high and the GH level must still be observed after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it was found that there may be a role for pre-operative medical management if tumor shrinkage can be achieved prior to surgery. Surgical outcomes may also be improved by lowering preoperative GH and IGF-I levels 4,5) . For residual tumor within the cavernous sinus area after medical or surgical treatment, gamma knife radiosurgery is a viable option.…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment, however, is commonly done for the patients who do not wish the surgery or who have not been cured by the surgery (Melmed et al 2009). Medical treatment is also carried out before the surgery in order to shrink the tumor size (Bush and Vance 2008). Dopamine agonists, also known as stimulators of GH secretion in healthy subjects (Eddy et al 1971), act as suppressors of GH secretion in patients with acromegaly and have been used for the medical therapy of acromegaly as well as prolactinoma (Thorner et al 1975).…”
Section: Introductionmentioning
confidence: 99%